Explaining budgetary indiscipline: evidence from spanish municipalities - Ignacio Lago-Pe\~nas; Santiago Lago-Pe\~nas (European Regional Science Association (ERSA), 2004)
The quest for political support drives to upward deviations from forecasted public deficits when i) budget procedures are soft, ii) breaking promises involving higher expenditures and lower taxes is costly in political terms, and iii) ex–post control by voters and political opposition is imperfect. This hypothesis is tested using data from Spanish municipalities during the period 1985-1995. Econometric estimates show that single-party majority incumbents are less prone to change forecasted budgets. While their forecasted deficits tend to be higher, they have lower actual deficits, which may be interpreted as the consequence of a higher consistency in the budgetary process. Secondly, upward deviations in deficit tend to rise in election years. While forecasted deficits are not different in election years, actual deficits are. Moreover, elections cause systematic downward deviations in revenues. On the contrary, the ideology of the incumbent is not relevant to explain deviations in deficit. Key words: Budget deficits, local governments, budget procedures, electoral promises. JEL CLASIFFICATION: H74
Keywords: H74; 330; Budget deficits; local governments; budget procedures; electoral promises